2015
DOI: 10.1039/c5nj00527b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and behaviour of ZnO-based nanocomposites designed for the control of biodeterioration of patrimonial stoneworks

Abstract: In this study, a preventive method for fighting bio-deterioration of stone substrates is proposed. This is\ud based on the use of bioactive zinc oxide nanoparticles (ZnO-NPs), which are able to exert a marked\ud biological activity over a long period of time due to their peculiar structure. ZnO-NPs are synthesised by\ud a simple and reproducible electrochemical procedure. The nanomaterials are embedded in consolidant/\ud water-repellent matrices to obtain nanostructured coatings. Commonly used products based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…In this paper, we report on the impregnation of various textiles with copper and zinc oxide nanomaterials in order to confer them antimicrobial properties. CuNPs and ZnONPs have been electrosynthesized and characterized following previous protocols; here, they are specifically investigated in the textile context, and a detailed surface spectroscopic investigation is used to fully characterize the modification of the textile products upon NPs impregnation. CuNPs have been prepared by means of sacrificial anode technique in the presence of tetraoctylammonium chloride as stabilizing agent and are characterized by nanometer‐sized diameter and narrow size dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report on the impregnation of various textiles with copper and zinc oxide nanomaterials in order to confer them antimicrobial properties. CuNPs and ZnONPs have been electrosynthesized and characterized following previous protocols; here, they are specifically investigated in the textile context, and a detailed surface spectroscopic investigation is used to fully characterize the modification of the textile products upon NPs impregnation. CuNPs have been prepared by means of sacrificial anode technique in the presence of tetraoctylammonium chloride as stabilizing agent and are characterized by nanometer‐sized diameter and narrow size dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…40 days in order to allow for complete drying of the surfaces, Silo111 and Estel1100 were applied two times by brush. These consolidant/water-repellents were used both as such and admixed with zinc oxide (0.4 % w/w) and copper (0.03 % w/w) nanoparticles, which were prepared by our research group [14,32].…”
Section: In Situ Experimentationmentioning
confidence: 99%
“…Commonly used tetraethoxysilane (TEOS)-and/or siloxanes-based materials (Estel1000, Silo111, and Estel1100) have been selected and the resulting nanomaterials have been fully characterised with XPS in order to determine the amount and speciation of the NPs available on the surface. Moreover, preliminary data [32] obtained by inductively coupled plasma mass spectrometry have shown that zinc is released when the coating is put in contact with acidified water, simulating rain conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide the material with antimicrobial activity, here we propose the addition of ZnO nanoparticles [13,14] to the aforementioned polymeric formulation [12]. We select these nanoparticles due to their confirmed chemical stability, biocompatibility, and bioactivity [15] and to their limited use in materials for stone conservation. Moreover, these nanoparticles may also provide superhydrophobicity to the material [16], which is also highly desired for coatings used for stone protection.…”
Section: Introductionmentioning
confidence: 99%